Chapter L'ordre dominicain dans le ciel du soleil. Dante Alighieri et la « viva giustizia » du Paradiso - Ricklin, Thomas (Reti Medievali E-Book, 2020)
This article analyses the dynamic role of Justice in Dante's Comedy. As the judge of his Otherworld, Dante establishes harsh punishments for the sinners in his Inferno. Moreover, he attacks their earthly fame in a way similar to what he experienced as an exile condemned to death by his Commune. Dante also defines the lighter penitences which torture the souls of his Purgatorio. Finally, Dante's Justice shines alive in his Paradiso, first in the sky of Mercury and then, at its apotheosis, in the sky of Jupiter, when the eagle an-wers Dante the Pilgrim's difficult questions about the salvation of pagan souls. As the eagle points out, even the blessed souls do not know the names of all the saved ones, and this remark should invite mortals to restrain from judging their peers. A similar message seems to be at the very heart of Aquinas' speech in the sky of the Sun.